Impact of Electric Vehicles and Demand Response Program on Optimal Operation of Distribution System in the Framework of a New Bi-level Model - S.Muhammad Bagher sadati; jamal moshtagh; miadreza Shafie-khah (مجله مدل سازی در مهندسی, 2018)
Abstract: In this paper, the impact of electric vehicles (EVs) and a price-based and an incentive-based demand response programs and the combination of both programs, has been investigated on the optimal operation of the distribution system, which owns a wind unit, in the framework of a new bi-level model. In this model, simultaneously, uncertainty of wind unit and electric vehicles are also considered. The aim of both levels is to maximization the profits. In the upper-level, the distribution system, due to the existence of a wind unit and the vehicle to grid capability of EVs, gains more profit by not purchasing the electrical energy from the upstream network. At the lower-level, owner of the EVs parking lots is obtained more benefit, due to the selling of energy to EVs owners and distribution system. Forasmuch as this model is converted to single-level mix-integer linear problem by using of Karush–Kuhn–Tucker (KKT) conditions and auxiliary binary variables and is solved by GAMS software. The presented model is tested on the IEEE 15-bus distribution system over a 24-h period and results prove the effectiveness of the model.